The Little Red Hen - Barton, Byron ([s.l.] : HarperCollins Big Book Edition, 1993)
The little red hen finds none of her lazy friends willing to help he plant, harvest, or grind wheat into flour, but all are eager to eat the bread she makes from it.
Keywords: Folklore; Children stories